The Development of Residential Areas on the Example of Łuków: Reurbanization and Suburbanization - Rafał Fornal; Artur Myna (Barometr Regionalny)
In planning documents, extensive land for housing is generally designed in the outskirts of cities. Suburbanization results in social costs and high costs of provision of technical and social infrastructure. The aim of the work is to develop and present a method of designating residential areas in such a way as to reduce the social and economic costs of spatial development of cities, improve spatial order and achieve long-term social benefits. In the example of Łuków, a vision of spatial development of a city was proposed by its reurbanization. New housing zones were designated near kindergartens, primary schools and basic health care facilities so that residents could reach them on foot. Maintaining the human scale of residential areas will limit traffic and its negative externalities. Areas that should not be used as land for housing construction were indicated to preserve ecological order. The change in spatial development of cities, from suburbanization to reurbanization, requires the pursuit of urban policy at all levels of public authority through the use of legal, planning, investment, financial, fiscal, property management, information and participation instruments.